Investigation of the damage and fracture of Ti-6Al-4V titanium alloy under dwell-fatigue loadings - Fernandes, Martin Ferreira [UNESP]; de Oliveira Velloso, Verônica Mara [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (Elsevier, 2021)
Ti-6Al-4V alloy turbine components for aeronautical applications operate at a steady state after reaching the maximum stress during each duty cycle. The load holds combined with the fatigue process causes a phenomenon called the dwell effect. The dwell periods reduce the fatigue strength of disks and blades of aeronautical turbine engines made of titanium alloys. In this work, trapezoidal dwell-fatigue and triangular fatigue tests were performed with a fatigue ratio of 0.1 at room temperature. The trapezoidal waveforms (dwell-fatigue tests) had a 10-second dwell period and 1-second loading and unloading rates for each fatigue cycle. The triangular waveforms (fatigue tests) were equivalent to trapezoidal waveforms with zero seconds at the maximum stress. The Weibull distribution was used to analyze the dwell-fatigue data statistically. The experimental results showed that the dwell-fatigue life debits for dwell periods of 10 seconds at stress levels of 1.0, 0.975, and 0.95 of the material yield strength were 10.2, 10.0, and 4.5, respectively. The results suggest that the dwell sensitivity of Ti-6Al-4V alloy increases at high-stress levels. The fracture of dwell-fatigue specimens occurred at a high-cumulated plastic strain and after a significantly lower fatigue life than at pure fatigue tests, indicating a substantial dwell-life debit of the Ti-6Al-4V alloy. The damage mechanism responsible for reducing the fatigue life when the dwell time was introduced was the plastic deformation accumulation observed in dwell-fatigue tests, possibly as a result of the stress redistribution mechanism in the α phase grains that leads to slip of dislocations and, consequently, early plastic deformation processes that instigate crack nucleation.
Keywords: Dwell-fatigue; Fatigue; Ti-6Al-4V; Titanium alloys; Turbine engines